A Critical Companion to Old Norse Literary Genre - Bampi, Massimiliano,Larrington, Carolyne,Rikhardsdottir, Sif,Schorn, Brittany,Kedwards, Dale,Rowe, Elizabeth Ashman,Goeres, Erin,Orning, Hans Jacob,Friðriksdóttir, Jóhanna Katrín,Quinn, Judy (Boydell & Brewer, Limited, 2020)
A comprehensive guide to a crucial aspect of Old Norse literature. Cover – Contents – List of Figures – Contributors – Acknowledgements – Abbreviations – Introduction – Genre – Hybridity – Terminology – Form – Orality, Textuality and Performance – Manuscripts and Codicology – The Body Politic – Geography – Time and Space – Memory – The Human Condition – God(s) – Wisdom – Skaldic Poetry - A Case Study – Eddic Poetry - A Case Study – Pӕttir - A Case Study – ĺslendingasǫgur - A Case Study – Byskupasögur and heilagra manna sögur - A Case Study – Romance - A Case Study – Annotated Taxonomy of Genres – Chronological Outline – Works Cited – Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books